A DESIGN OF INTERNET CONTROL OF THINGS FLOOD LIGHT AT AIRPORTS - Zelika Argyanti; Amani Darma Tarigan; Zuraidah Taro (Sean Institute, 2023)
This paper describes the Flood Light control system provided on the apron, or on a part of the apron, and in isolated parking positions that have been found, which is useful for helping smooth operational activities at the airport, especially at night and security for aircraft in flight. Parking is also designated for loading and unloading activities of goods and passengers. IoT (Internet of Things) can be used in buildings to control electronic equipment such as lights which can be operated remotely via a computer network or smartphone.